2021
DOI: 10.1016/j.isci.2021.102739
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin-related transcription factor and serum response factor regulate cilium turnover by both transcriptional and local mechanisms

Abstract: MRTF and SRF are required for primary cilium (PC) resorption MRTF and SRF localize to the basal body/PC and interact with ciliary proteins MRTF/SRF impact cilium turnover also by nontranscriptional, local mechanisms MRTF interacts with CEP290 and inhibits ciliogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
0
4
1
Order By: Relevance
“…Dynlacht, 2018). Previous reports have suggested that the upregulation of these molecules enhances the resorption of primary cilia (Oh et al, 2022;Speight et al, 2021). In our study, however, we did not observe any changes in these genes, suggesting that LIF-induced shortening of cilia might be achieved by another approach (Table S1).…”
Section: Lif and Ccl2 Influence Primary Cilia Length Of Non-immortali...contrasting
confidence: 75%
See 1 more Smart Citation
“…Dynlacht, 2018). Previous reports have suggested that the upregulation of these molecules enhances the resorption of primary cilia (Oh et al, 2022;Speight et al, 2021). In our study, however, we did not observe any changes in these genes, suggesting that LIF-induced shortening of cilia might be achieved by another approach (Table S1).…”
Section: Lif and Ccl2 Influence Primary Cilia Length Of Non-immortali...contrasting
confidence: 75%
“…The length of primary cilia is thought to be determined by the balance between the cilium assembly and disassembly mechanisms, and the known molecules composing cilium disassembly machinery include CPAP, Aurora A, Histone Deacetylase 6 (HDAC6), Polo Like Kinase 1 (PLK1), and Kinesin Family Member 24 (KIF24) (Ishikawa & Marshall, 2011; Liang et al, 2016; Wang & Dynlacht, 2018). Previous reports have suggested that the upregulation of these molecules enhances the resorption of primary cilia (Oh et al, 2022; Speight et al, 2021). In our study, however, we did not observe any changes in these genes, suggesting that LIF‐induced shortening of cilia might be achieved by another approach (Table S1).…”
Section: Discussionmentioning
confidence: 94%
“…The analysis of cytoplasmic SRF using green fluorescent protein (GFP)-fused SRF lacking a nuclear localization signal (SRF-ΔNLS-GFP) demonstrated the extranuclear roles of SRF, which were associated with the actin-severing factor cofilin, to regulate axonal outgrowth and branch formation (Stern et al, 2013 ). Furthermore, there is other evidence for a local role of MRTF and SRF in cilium turnover (Speight et al, 2021 ). Therefore, it would be interesting if MRTF interacts locally with SRF in the cytoplasm to regulate neuronal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, as an attempt to use WNT pathway components as potential drug targets for treating bone diseases, it was shown that inhibition of SFRP1 led to increased total bone area in a murine calvarial organ culture assay (Bodine et al, 2009) and to an elevated bone synthesis activity in ovariectomy-induced osteoporotic of cilia-associated proteins have a nuclear presence and potentially nuclear roles (McClure-Begley & Klymkowsky, 2017). For example, dual roles were previously described for myocardin-related transcription factor and serum response factor that act both as transcription factors and as primary cilia constituents impacting ciliary protein-protein interactions (Speight et al, 2021). It is therefore conceivable that intact TAPT1 at the centrosome/ciliary base could interact with transcription-modulating proteins and regulate their nuclear translocation.…”
mentioning
confidence: 97%
“…It is increasingly evident that a number of cilia‐associated proteins have a nuclear presence and potentially nuclear roles (McClure‐Begley & Klymkowsky, 2017 ). For example, dual roles were previously described for myocardin‐related transcription factor and serum response factor that act both as transcription factors and as primary cilia constituents impacting ciliary protein–protein interactions (Speight et al , 2021 ). It is therefore conceivable that intact TAPT1 at the centrosome/ciliary base could interact with transcription‐modulating proteins and regulate their nuclear translocation.…”
mentioning
confidence: 99%